(untitled) (REMUNOM, 2026)
This article investigates the connections between structural racism, migration policies, and social hope in Brazil, focusing on the state of Rio de Janeiro. It adopts a qualitative, exploratory-analytical approach, guided by a critical and decolonial perspective, configuring itself as bibliographic and documentary research, with thematic content analysis and a case study. The theoretical framework draws on contributions from Brazilian social thought, decolonial critique, anti-discrimination law, and emancipatory pedagogies. The analysis reveals that structural racism is a historically constituted and re-actualized system, and that the Brazilian State has acted to perpetuate racial inequalities through the Land Law (1850), subsidized immigration policies for Europeans, and law as a technology of racialization. Structural barriers to Black immigrants persist, revealing ethno-racial selectivity. In Rio de Janeiro, necropolitics operates as a differential management of Black lives, while collectives such as Mães de Acari and Mães de Manguinhos emerge as resistance. Social hope, a collective political force, materializes in affirmative action, decolonial pedagogies, and engagement with future generations. It is concluded that confronting structural racism requires a profound transformation of social, economic, and symbolic structures, articulating social hope, political organization, and pressure from social movements.